PENGARUH SEX EDUCATION MENGGUNAKAN MEDIA WHEEL OF FORTUNE TERHADAP PREVENTIF SEXUAL ABUSE ANAK USIA DINI DI TK SELARAS CITA - KOTA MALANG - Dewi Ayu Nurmanignsih; suprapti suprapti suprapti; Ari Kusmiwiyati (Jurnal Pendidikan Kesehatan, 2021)
The time of children is often referred to by the term The Golden Age. Early childhood takes control of adults in the process of child development. Many children experience developmental problems one of which is sexual violence. According to Pramastri 2014, sexual assault is sexual activity in children who do good by adults, as well as the children of peers with the victim. One way of addressing the problems of the high number of sexual assaults on children is providing sex education in early childhood. Media Wheel of Fortune this can encourage children to participate in learning. Therefore, this Wheel of Fortune media provide feedback directly. The design of this study using One Group Pre Test Post Test design with a population of 33 children, using the technique of sampling Simple Random Sampling, with the number of samples 30 children who meet the criteria for inclusion. Data retrieval is performed using ceklist as a research instrument. Then the data were analyzed using SPSS the test with wilcoxon signed rank test, p equal 0.05, indicates that the value significance of 0.007. Therefore the value of significance p 0.05 greater then H0 is rejected, meaning rejected, meaning there are influences of sex education using media wheel of fortune against preventive early childhood sexual abuse at Selaras Cita Kindergarten in Malang City. Expected health workers specifically midwives can be used as input in the prevention of child sexual violence and make other programs related to sex education for children.